REVALUATIONS OF FIXED ASSETS. - Weston, J. Fred (The Accounting Review, 1953)
Sound principles of asset valuation provide a basis for approximations of current values. The major objection to the adoption of theoretically defensible principles of valuation and associated cost measurements is the opinion that difficulties of practical implementation are insuperable. This argument is considerably weakened by the fact that revaluations of assets take place in practice. Empirical studies demonstrate that the large magnitude of such adjustments results in important effects on net income. There is little evidence to indicate the nature of the considerations which guided such adjustments. It is suggested that if the fact of asset value increases were recognized in general accounting practice, the likelihood of the achievement of objective standards would be improved. Additional objections to the economic principle of asset valuation and associated cost measurement procedures are considered. The assertion that incorrect expense measurement has little significance for price policy is true only under a special set of narrow assumptions. The objection that identical physical assets are not, in practice, replaced is met by the provision that source of similar services will be replaced. If in replacement it is desired to produce a different type of services, this raises a problem not relevant to the valuation issue. Another suggested reason for disregarding value changes is that such value changes are self-canceling. This assumes a symmetry in cyclical fluctuations which is not demonstrable. It ignores changes in values resulting from changes in the economic structure or secular changes. The non-recognition of the economic principle of valuation in accounting regulations established by governmental agencies is also cited as a basis for its rejection. There is circularity involved here, however. In large measure, government tax regulations seek to reflect the best "recognized accounting principles."